Secondary Intraocular Lens Options in Intraocular Lens Dislocation: A Review - Alexander Maloof; Ava James; Nicholas Pavic; Shane Zhang; Stephanie Wu; Christopher Go (TNOA Journal of Ophthalmic Science and Research)
Intraocular lens dislocation is an uncommon complication of cataract surgery. This review presents an updated summary of the secondary intraocular lens (IOL) options that are described in the literature for the management of IOL subluxation or dislocation. A broad review of the literature was performed. We evaluated different techniques for both IOL lens rescue and secondary IOLs, with a focus on the latter. We structured our review of each option by the salvageability of the IOL, the preservation of the bag, and subsequently the adequacy of capsular support. We then evaluated the techniques available for each option, with a clinical focus on the anatomical indications, technical considerations, advantages, and potential complications, before proposing an algorithm for determining the selection of each major secondary IOL implantation technique. While there are numerous IOL techniques and lens options for addressing IOL dislocation, there is currently no consensus on the optimal method. The choice of secondary IOL and fixation techniques are often guided by patient anatomy and the nature of the dislocation, but in many cases are decided upon the surgeon’s experience and preference.